PENERAPAN CONTEXTUAL TEACHING AND LEARNING BERBASIS CERITA RAKYAT ETNIS NGADHU BHAGA UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS SEKOLAH DASAR - Vinsensius Pala; Yosefa Awe, Ermelinda; Patrisia Wau, Maria; Laba Laksana, Dek Ngurah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The use of the Contextual Teaching and Learning (CTL) approach combined with local ethnic folklore is an alternative learning method that can connect material to the context of students' lives, thus potentially improving critical thinking skills. However, the implementation of local culture-based contextual learning in Indonesian language learning is still not optimal, so students' critical thinking skills need to be improved. This study aims to determine the effectiveness of the Contextual Teaching and Learning (CTL) approach based on Ngadhu-Bhaga ethnic folklore in improving critical thinking skills of grade VI A students of SDK Regina Pacis Bajawa. This study used the Classroom Action Research (CAR) method with the Kemmis and McTaggart design, which was implemented in three cycles. The research subjects were 22 students, while the object of the research was students' critical thinking skills on narrative text material. Data were collected through observation, interviews, tests, and documentation. The research instruments included observation sheets of teacher and student activities, interview guidelines, critical thinking skills tests, critical thinking skills assessment rubrics, and documentation. Data were analyzed descriptively qualitatively and quantitatively. The results showed an increase in students' critical thinking skills in each cycle. The average value of critical thinking ability increased from 54.77 in the pre-action stage to 65.00 in Cycle I, 75.68 in Cycle II, and 82.27 in Cycle III. This increase indicates that the implementation of CTL based on Ngadhu-Bhaga ethnic folklore is able to encourage active student involvement and help them connect learning materials with local experiences and cultural environments. Thus, the CTL approach based on Ngadhu-Bhaga ethnic folklore is effective in improving students' critical thinking skills and creating more meaningful and contextual Indonesian language learning.